Evaluation of Introductory Environmental Chemistry Course for Prospective Chemistry Teachers Using Context, Input and Process Models - Widyaningsih, Mia; Nahadi, N; Mudzakir, Ahmad; Sriyati , Siti; Khoerunnisa, fitri (Journal of Tropical Chemistry Research and Education, 2024)
This study aims to evaluate the learning programme of the Introduction to Environmental Chemistry course of the Chemistry Education study programme in one of the public universities in Bandung City. This study needs to be evaluated and improved because there are still aspects that are not in accordance with 21st century learning as evidenced by document analysis and learning observations. The method used is a qualitative approach and the CIPP (Context, input, process, Product) evaluation model as a tool to evaluate and improve the lecture programme which focuses on the Context aspect in the form of document analysis of the Semester Learning Plan (SLP), the Input aspect in the form of lecturer interviews and the Process aspect in the form of learning observations. The results obtained from the analysis show that there are several findings that need to be evaluated due to the incompatibility of aspects in the SLP document update such as administrative completeness, the General Skills Aspect (GSA) 1 listed is not in accordance with the Context of Learning Outcomes (CLOs), based on interviews with teaching lecturers it is stated that problem-based learning (PBL) with the context of validated environmental issues in relevant theoretical content and in the aspect of the learning observation process it was found that there were aspects of learning practices that were not in accordance with the SLP document reference. The evaluation also highlighted the importance of updating and adjusting learning media to be more interactive and relevant to the context of environmental issues. The assessment of the last three years shows the potential to further develop programmes can to improve students' higher order thinking skills